Transformasi Digital dan Kewirausahaan Syariah di Era Modernitas : Peluang dan Tantangan dalam Ekonomi Syariah di Indonesia - Farah Qalbia; M. Reza Saputra (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2024)
Digital transformation in Indonesia presents significant opportunities and challenges for the Islamic economy, particularly in digital-based entrepreneurship. This study aims to analyze the potential and barriers to implementing Islamic digital entrepreneurship and the role of technology in enhancing financial inclusion and business efficiency. The research employs a qualitative method with a literature review approach, examining relevant studies on the development of Islamic fintech, halal e-commerce, and blockchain technology. The findings show that Islamic digital entrepreneurship has the potential to expand global market access, improve transaction transparency, and strengthen adherence to Sharia principles. However, significant obstacles such as low financial digital literacy and the complexity of Sharia regulations still need to be overcome. Additionally, cross-sector collaboration and an increase in digital literacy within society are required in order to support the development of an inclusive and sustainable Islamic economy. The conclusion of this study emphasizes the importance of digital technology integration in Islamic entrepreneurship as a strategic step to strengthen the stability of the Islamic economy amid global changes.